FIRST RECORDS OF FRESHWATER FISHES GARRA GRAVELYl AND G. KEMPl IN MANIPUR - Vishwanath, W; Singh, H Tombi; Singh, O Shashikumar; Sharma, M Gonchandra (Indian Journal of Fisheries, 2011)
Two species of Cyprinid hill stream fishes Garra gravelyi (Annandale) andG. kempi Hora are recorded and described from the streams of Chindwin Drainage,Manipur State.